EMERALD EXTRACTIVISM: BORDERS, ENERGY, AND DATA INFRASTRUCTURES IN IRELAND - Brodie, Patrick (AoIR Selected Papers of Internet Research, 2023)
In November 2020, a video surfaced on Twitter showing the earth moving underneath the feet of a local hillwalker. The video documented a massive peat landslide at the border between Ireland and Northern Ireland, caused by the construction of the Meenbog Wind Farm. The landslide destroyed a swathe of active peat bog and polluted a watershed which spanned both sides of the border, prompting governmental and legal action from agencies and organizations in Ireland, Northern Ireland, and UK. A key piece of the puzzle, however, was that the Meenbog Wind Farm had in 2019 sold its future energy to global logistics and cloud giant Amazon to power its data centre operations in Dublin, over 200km away from this wind farm site in rural Donegal. The data infrastructure company’s decarbonization efforts were following fault lines and toxic legacies of colonial expansion, the imagined perpetual growth of data systems having unintended consequences at Ireland’s contested internal border. By analyzing data centre and energy policy, public discourse around these infrastructural systems, and drawing upon site-specific fieldwork, this paper will confront the re-organization of political and environmental relations at the border with regards to emerging renewable energy and data entanglements. Engaging with vibrant discourses of “green extractivism” during the transition to renewable energy, the paper will approach bordering mechanisms cutting through Ireland as sites of contestation about what present and future extractive energy and data supply chains will look like, who will bear their burdens, and who will have a voice in shaping them.